Pengaruh Kualitas Produk, Equitas Merek, Persepsi Konsumen, Store Atmosphere Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Café Pondok Cendana Rantauprapat - Aprianda, Dimas; Pitriyani, Pitriyani; Halim, Abd. (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to analyze the effect of product quality, brand equity, consumer perceptions, store atmosphere and service quality on purchasing decisions at Café Pondok Cendana Rantauprapat. This type of research is quantitative, the place of this research is Café Pondok Cendana Rantauprapat. The data collection techniques used in the study were observation, documentation and questionnaires using a Likert scale. The population in this study were consumers of Café Pondok Cendana Rantauprapat. To simplify the sample size, researchers used the formula submitted by Ferdinand (2014). Thus, the number of samples in this study were 125 respondents. The data collection techniques used in the study were observation, documentation and questionnaires using a Likert scale. In this study using multiple linear regression analysis tested with partial (t), simultaneous (F) and coefficient of determination tests. The results showed that product quality, brand equity, consumer perceptions, store atmosphere and service quality simultaneously had a positive and significant effect on purchasing decisions at Café Pondok Cendana Rantauprapat.